PENGARUH ETIKA ISLAM TERHADAP SIKAP TOLERANSI DAN KETERBUKAAN PADA PENDIDIKAN DASAR MULTIKULTURAL BERBASIS MODERASI BERAGAMA - Luluk Mascluhah; Marfu'ah Marfu'ah; Ida Rahmawati (Program Studi Pendidikan Agama Islam, 2024)
This study examines the influence of Islamic ethics on tolerance and openness in multicultural education based on religious moderation at the elementary education level. Utilizing a quantitative approach with a quasi-experimental design, this research involves students divided into experimental and control groups. The findings indicate that integrating Islamic ethics with religious moderation significantly enhances students' tolerance and openness. The experimental group, which received Islamic ethics-based education, demonstrated increased tolerance toward cultural differences and openness to diverse values. These findings underscore the importance of applying moderate Islamic values in multicultural education as an effort to form an inclusive and harmonious generation amidst diversity.